Ekologik smart bog‘cha Ta’limda innovatsiyalar va barqaror rivojlanish - Hoshimova Dilnoza (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article is dedicated to the in depth Study of the nature of ecological smart kindergartens and their place in the field of education Kindergartens combine the principles of sustainable development with modern technologies to form children's ecological cons-ciousness and serves to effectively organize the educational process.